Peranan Komunikasi dalam Jasa Keagenan untuk Meningkatkan Kepuasan Pemilik Kapal (Ship Owners) pada PT. Gemalindo Sukses Bahari Dumai - Aldi Pranata Siregar; Syarifur Ridho; Lilis Lilis (Indonesian Maritime Researchers and Lecturers, 2026)
This study examines the role of communication in agency services to improve shipowner satisfaction at PT. Gemalindo Sukses Bahari in Dumai. As a company engaged in the field of ship agency, PT. Gemalindo Sukses Bahari has an important responsibility in establishing effective communication with shipowners to ensure smooth operations and satisfactory service. The purpose of this study is to analyze how the communication strategy implemented by the company can affect the level of satisfaction of shipowners, as well as to identify the communication factors that are most influential in building professional and trustworthy working relationships. The research method used is a qualitative approach with research data obtained through interviews, observations, and document reviews. The findings indicate that transparent, responsive, and informative communication between agents and shipowners has a significant influence on increasing customer satisfaction. In addition, the use of appropriate communication media, timeliness in delivering information, and the agent's interpersonal skills are key elements in maintaining harmonious working relationships. This study concludes that effective communication is the main foundation for the success of ship agency services and has a direct impact on shipowner satisfaction and loyalty.